Zhihar Contextualization in Indonesia: an Anthropo-Linguistic Study - Siradjudin, Azmi; Maliki, Ibnu Akbar (Universitas Islam Negeri Raden Intan Lampung, 2022)
The law of zhihar (equating wife to her mother) is closely related to Arabic culture, where the Qur'an was revealed. In Indonesia, zhihar law cannot be enforced because of social norms differences. This article examines the contextualization of zhihar in Indonesia. The aim is to examine the meaning of zhihar in the Qur’an which is then applied in the context of Indonesian culture. Specifically, the contextualization includes the use of language in the zhihar which is then linked to the existing cultural context. This research is purely a literature study using qualitative methods. The approach used is the sociology of language, or more specifically it can be called the anthropo-linguistic approach. The results of the study show that respect is deeply embedded in family life in Indonesia. This means that the husband may equate his wife with his mother-in-law; But not forbid himself against his wife, only to praise and respect her. From the perspective of the sociology of language, this compliment is a reflection of cultural values that have long lived in Indonesian society. The mufassirs (the commentators of al-Qur'an) stated that this action is not zhihar because the lafadz zhihar requires the intention to forbid husband and wife relations. Therefore, it is necessary to conduct an in-depth study dealing with the axiological value of the law of zhihar in the Qur'an which is linked to socio-cultural aspects.